Perspective for removing volatile organic compounds during solar‐driven water evaporation toward water production. Issue 6 (18th October 2021) - Ma, Jiaxiang; Xu, Ying; Sun, Feiyun; Chen, Xiaodong; Wang, Wei
Abstract: Solar evaporation has attracted considerable interest to alleviate the shortage of water resources in the past few years. Lots of works have been done focusing on evaporation materials, rate, and efficiency, however, little attempts have been made to remove the harmful volatile organic compounds (VOCs), a kind of contamination that inevitably evaporate and condense alongside with water, which seriously affect the distilled water quality. This perspective puts forward some technical ideas utilizing chemical or physicochemical methods, aiming at the development of multifunctional composite materials, and forming an integrated evaporation system, which manage to remove VOCs in situ at the interface of photothermal evaporation. Abstract : Technical ideas utilizing chemical or physicochemical methods for volatile organic compounds (VOCs) removal are put forward in this perspective, aiming at the development of multifunctional composite materials, and forming an integrated evaporation system, which manage to remove VOCs in situ at the interface of photothermal evaporation. This perspective also serve as a guidance for future materials design.